2020
DOI: 10.1108/ijaim-10-2019-0117
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit organization fraud reporting: does governance matter?

Abstract: Purpose This paper aims to contribute to the extant literature in this field by examining nonprofit organizations’ fraud reporting compliance using logistic regression and decision tree induction algorithms. Design/methodology/approach This study used the data from 428 nonprofit organizations during 2009-2015 period, and analyzed 21 individual measures (obtained from these organizations’ Internal Revenue Service Form990 filings) using logistic regression and decision tree induction algorithms, to study the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 41 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…Ohalehi (2019) emphasizes the significance of an internal control system and a better governance structure (good corporate governance) for philanthropic institutions of all sizes to protect themselves from potential fraud. Abu Khadra and Delen (2020) emphasized the significance of implementing good corporate governance (GCG) in combating fraud. Moreover, Wahyuni-TD et al (2021) tested the effects of GCG and fraud prevention on the performance of zakat institutions with positive results, but there was no significant effect of the principle of fairness of GCG on zakat performance with fraud prevention, indicating that zakat institutions should pay more attention to the application of justice to avoid fraud, and the principle of justice is an early signal that can be used to detect whether there is fraud.…”
Section: Introductionmentioning
confidence: 99%
“…Ohalehi (2019) emphasizes the significance of an internal control system and a better governance structure (good corporate governance) for philanthropic institutions of all sizes to protect themselves from potential fraud. Abu Khadra and Delen (2020) emphasized the significance of implementing good corporate governance (GCG) in combating fraud. Moreover, Wahyuni-TD et al (2021) tested the effects of GCG and fraud prevention on the performance of zakat institutions with positive results, but there was no significant effect of the principle of fairness of GCG on zakat performance with fraud prevention, indicating that zakat institutions should pay more attention to the application of justice to avoid fraud, and the principle of justice is an early signal that can be used to detect whether there is fraud.…”
Section: Introductionmentioning
confidence: 99%
“….Information disclosure can track and monitor the activities and programs organized by the NPOs. However, this is depends on the degree of the information that being disclosed and how transparent and accountable is the NPO (Khadra & Delen, 2020;Skoczylas-Tworek, 2020). This is because in some cases even in the annual report, there are still fraud occurred.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Numerous studies have examined the impact of corporate boards in organisations and have reported significant associations between their governance role and various areas such as the auditor quality choice/fraud reporting (Karim et al, 2013;Abu Khadra and Delen, 2020), dividend payout policy (Al-Najjar and Kilincarslan, 2016;Elmagrhi et al, 2017), earnings characteristics/quality (Ji et al, 2015;Yu and Wang, 2018), firm performance/valuation (Brown and Caylor, 2006;Siddiqui, 2015;Khosa, 2017), corporate social responsibility and environmental disclosures (Ullah et al, 2019;Kilincarslan et al, 2020), and risk taking behaviour measured by credit risk (Ko et al, 2019) or R&D intensity (AlHares et al, 2020). Indeed, the agency-based-explanation framework emphasises the control role of the board of directors in monitoring executives' discretion and suggests that internal governance mechanisms provided by the structure of the board (e.g., board size, board independence and chairman/chief executive officer (CEO) duality) help to ensure that boards serve as a trustworthy agent to maximise shareholders' wealth and increase firm value Weir and Laing, 2003;Guest, 2009).…”
Section: The Agency Theory On Corporate Governance and Firm Performancementioning
confidence: 99%